Implementasi AR dan LMS untuk Meningkatkan Kompetensi Siswa SMK : Studi Kasus Jurusan Perhotelan - Irwansyah Irwansyah; Tata Sutabri (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the effectiveness of the integration of Augmented Reality (AR) technology and Learning Management System (LMS) on improving the skills of vocational high school students majoring in hospitality and culinary arts. Qualitative findings show time efficiency, technical challenges, and training needs. This study recommends the integration of WebXR-based AR to overcome the limitations of device specifications in vocational high schools. Objective: To assess the effectiveness of AR and LMS in improving practical skills and learning management in vocational high schools. Method: Mixed-method research with quasi-experimental (30 hospitality students, 30 culinary students) and LMS analysis using log activity data from Moodle. Results: AR improves the understanding of housekeeping practices by 28% (paired sample t-test, p<0.05), while LMS reduces teacher administration time by 40%. Conclusion: AR-LMS integration has the potential to be a cost-effective solution for vocational high schools.